2019
DOI: 10.1111/pcn.12913
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tipepidine as adjunctive therapy in children with attention‐deficit/hyperactivity disorder: Randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Aim: This study evaluated the efficacy and safety of tipepidine as an add-on to methylphenidate in the drug treatment of attention-deficit/hyperactivity disorder (ADHD).Methods: This study was an 8-week, randomized, parallel group, double-blind, placebo-controlled trial recruiting 53 ADHD-diagnosed children. Patients were randomly divided to receive methylphenidate + tipepidine or methylphenidate + placebo for 8 weeks. Participants were assessed using the parent version of ADHD Rating Scale-IV and the Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…In addition to depression, tipepidine has shown beneficial therapeutic effects in other psychiatric disorders involving the dopaminergic system. In this regard, in a recent randomized, double‐blind clinical trial, we demonstrated that add‐on treatment with methylphenidate and tipepidine improved hyperactivity‐impulsivity of attention deficit hyperactivity disorder 56 . The findings of the current study are in agreement with previous clinical findings, showing that adjunctive treatment with citalopram and tipepidine significantly improves severity of depression in patients with MDD.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to depression, tipepidine has shown beneficial therapeutic effects in other psychiatric disorders involving the dopaminergic system. In this regard, in a recent randomized, double‐blind clinical trial, we demonstrated that add‐on treatment with methylphenidate and tipepidine improved hyperactivity‐impulsivity of attention deficit hyperactivity disorder 56 . The findings of the current study are in agreement with previous clinical findings, showing that adjunctive treatment with citalopram and tipepidine significantly improves severity of depression in patients with MDD.…”
Section: Discussionsupporting
confidence: 91%
“…These trials have reported its efficacy in pediatric patients with ADHD at the same dose as the original indication of antitussives (30 mg/day). In a recently reported Iranian placebo-controlled study, in which tipepidine is added to methylphenidate, its effect on ADHD was confirmed at the same dose as antitussives, although the study design was different from that of the TS-141 phase II study [29].…”
Section: Discussionmentioning
confidence: 97%
“…These trials have reported its efficacy in pediatric patients with ADHD at the same dose as the original indication of antitussives (30 mg/day). In a recently reported Iranian placebo-controlled study, in which tipepidine is added to methylphenidate, its effect on ADHD was confirmed at the same dose as antitussives, although the study design was different from that of the TS-141 phase II study [ 29 ]. Conversely, the upper dose was set to 120 mg, the maximum dose of Asverin to reduce the clinical data package for application using the abundant safety profile of Asverin.…”
Section: Discussionmentioning
confidence: 99%